Learning descriptors for sequence-based hierarchical place recognition - Lan, Xin (Nanyang Technological University, 2022)
Visual place recognition aims at making unmanned vehicles recognize a revisit place of their exact location and returning reasonable query information. Most researchers regard this kind of problem as an image retrieval task. There are mainly two categories in this task: the hand-crafted feature extraction method and the learning-based feature representation method. This dissertation will focus on the latter.